2020
DOI: 10.1186/s12887-020-02415-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 10 children with a pediatric inflammatory multisystem syndrome associated with COVID-19 in Iran

Abstract: Background Although symptoms and signs of COVID-19 (Coronavirus disease 2019) in children are milder than adults, there are reports of more severe cases which were defined as pediatric inflammatory multisystem syndrome (PIMS). The purpose of this report was to describe the possible association between COVID-19 and PIMS in children. Methods From 28 March to 24 June 2020, 10 febrile children were admitted with COVID-19 infection showin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 14 publications
0
28
1
1
Order By: Relevance
“…When focusing on severe abdominal manifestations, we found nine patients affected by MIS-C who underwent exploratory laparotomies: two children with a healthy appendix as finding (“pseudo appendicular syndrome”) [ 16 , 17 ], one with aseptic peritonitis [ 18 ], four with appendicitis [ 19 ] and two with mesenteric lymphadenitis [ 20 ]. Appendicitis was initially suspected in roughly 5–30% [ 16 , 18 , [20] , [21] , [22] , [23] , [24] ] of the reviewed case series and in four case reports [ 9 , 17 , 25 , 26 ]. Three patients underwent intestinal resection with re-anastomosis due to segmental inflammation with necrosis of terminal ileum [ 9 , 17 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When focusing on severe abdominal manifestations, we found nine patients affected by MIS-C who underwent exploratory laparotomies: two children with a healthy appendix as finding (“pseudo appendicular syndrome”) [ 16 , 17 ], one with aseptic peritonitis [ 18 ], four with appendicitis [ 19 ] and two with mesenteric lymphadenitis [ 20 ]. Appendicitis was initially suspected in roughly 5–30% [ 16 , 18 , [20] , [21] , [22] , [23] , [24] ] of the reviewed case series and in four case reports [ 9 , 17 , 25 , 26 ]. Three patients underwent intestinal resection with re-anastomosis due to segmental inflammation with necrosis of terminal ileum [ 9 , 17 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…When considering imaging studies, ileitis or colitis were present approximately in 4–28% of cases [ 6 , 7 , 13 , 23 , [27] , [28] , [29] , [30] , [31] ]. Moreover, a diagnosis of mesenteric adenitis in MIS-C has been accounted by 8 case-series, with a prevalence of 9–20% of the abdominal imaging studies [ 6 , 8 , 13 , 16 , 23 , 27 , 31 , 32 ]. In addition, the latter condition has been also described in six recent case-reports from different geographic areas [ 9 , 25 , 26 , 30 , 33 , 34 ]: notably, in one of those patients mesenteric lymphadenitis was even confirmed on surgical specimens by pathologists [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Whittaker et al reported two giant CAAs ( z -score >10) in children with multiple systemic inflammations during the COVID-19 pandemic. The involvement of coronary arteries in COVID-19-associated MIS-C patients, even in the absence of typical criteria for KD, indicates the need for more attention to these vessels, especially if the patient has symptoms of shock or severe systemic inflammation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A handful number of hospitalized cases in infants and children were reported compared to adults in hospitals in Navarra, Spain during the first wave of the COVID-19 outbreak (February–May 2020) [ 14 ]. Ten febrile children were hospitalised with COVID-19 infection demonstrating characteristics of PIMS in northern Iran from 28th March to 24th June 2020 [ 15 ]. First such case in India was reported from Chennai on the 10th May, 2020 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%